Menciptakan Keadilan dengan Penerapan Hukum Progresif Melalui Pendekatan Ilmu Ketuhanan - Ridwan Ridwan (Universitas Syiah Kuala, 2012)
ABSTRACT: Repressive criminal law ia a phenomena warrying people. One of the causes of it is narrow undersanding of the law that the law is always considered as te act and the law centainty is a same as the act certainty. The maturity of understanding representing law is an act then delivering the view that the most important is the law centainty cousing that the justice of law is ignored, and also criticism amongst the lawyers. It results in repressive law offering solution for the delay of justice. This law is based on the principle that the law is made for human being hence the law is supporting the people and justice. Therefore, the meaning of the principle is not just written law but also the living law that is unwritten. Bringging Justice by the Application of Progressive Law Through Theological Approach